Evaluation of anti-arthritic effect of Torilis leptophylla and its comparison with indomethacin: Anti-arthritic effect of Torilis leptophylla with indomethacin (Journal of Fatima Jinnah Medical University, 2020)
Background: Rheumatoid arthritis is an autoimmune debilitating disease involving multiple joints and organs. Many treatment options are available but all are associated with frequent side effects. Phytochemical screening of Torilis leptophylla has shown the presence of anti-inflammatory compounds like flavonoids, phenols and anthraquinones. This study was designed to evaluate its effect on joints inflammation (rheumatoid arthritis). Indomethacin is one of the oldest and most commonly used drugs for arthritis. It was used as a standard drug to compare with indomethacin.Methods: This experimental study was carried out in Pharmacology Department, University of Health Sciences, Lahore. Thirty six male albino Wistar rats were randomly divided into six groups (group I-control, group II-positive control, group III-10 mg indomethacin, group IV,V,VI--100mg, 200mg, 300mg Torilis leptophylla extract (TLE) administered (orally) respectively). Arthritis was induced by sub plantar injection of 0.1 ml Freund’s complete adjuvant (FCA) to all groups except the control group. Body weight (weekly) and ankle joint diameter (every 4th day) were measured. At day 29 blood was collected and all animals were killed by overdose of ether. Acid phosphatase and alkaline phosphatase levels were determined by chemistry analyzer (RX MONZA, RANDOX, Republic of Ireland). Statistical analysis was performed using SPSS 20. One way ANOVA and Post hoc -Tukey tests were applied. A p-value of ≤0.05 was considered statistically significant.Results: Treatment with indomethacin caused significant (p≤0.001) reduction in all the inflammatory parameters. Torilis leptophylla extract also significantly (p≤0.05) reduced all the inflammatory parameters. Anti-inflammatory effect was comparable to indomethacin.Conclusion: Torilis leptophylla has significant anti-arthritic activity as it modified the parameters of joint inflammation and destruction.
Keywords: Rheumatoid Arthritis; Freund’s Complete Adjuvant; Torilis leptophylla; Indomethacin; Anti-inflammatory